2020
DOI: 10.1096/fj.202001495r
|View full text |Cite
|
Sign up to set email alerts
|

Branched chain amino acids and carbohydrate restriction exacerbate ketogenesis and hepatic mitochondrial oxidative dysfunction during NAFLD

Abstract: Mitochondrial adaptation during non-alcoholic fatty liver disease (NAFLD) include remodeling of ketogenic flux and sustained tricarboxylic acid (TCA) cycle activity, which are concurrent to onset of oxidative stress. Over 70% of obese humans have NAFLD and ketogenic diets are common weight loss strategies. However, the effectiveness of ketogenic diets toward alleviating NAFLD remains unclear. We hypothesized that chronic ketogenesis will worsen metabolic dysfunction and oxidative stress during NAFLD. Mice (C57… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 54 publications
(207 reference statements)
0
9
0
Order By: Relevance
“…Recently, improvement of adult-onset mitochondrial myopathy was achieved by intervention of NAD + levels with niacin ( 41 ). Moreover, the protection of liver function through supplement of branched amino acids has also been reported ( 42–45 ). Altogether, these studies suggest that supporting the metabolic balance might be a treatment strategy to be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, improvement of adult-onset mitochondrial myopathy was achieved by intervention of NAD + levels with niacin ( 41 ). Moreover, the protection of liver function through supplement of branched amino acids has also been reported ( 42–45 ). Altogether, these studies suggest that supporting the metabolic balance might be a treatment strategy to be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Given the insulin secretion stimulatory effect of BCAAs on β-cells [ 130 ], the high levels of BCAAs observed in obesity and T2DM may suggest a deleterious long-term effect or resistance to their function similar to what happens to FGF-21 in obesity [ 128 , 129 , 138 ]. Restriction of BCAAs was reported recently to worsen ketogenesis and cause oxidative dysfunction of the mitochondria in mice [ 206 ]. A ketogenic diet could be a useful approach to burn excess calories and harness less energy by the cell theoretically, although randomized controlled trials have shown only a minor effect [ 207 ].…”
Section: Mechanisms Of Remission Of T2dm After Weight Lossmentioning
confidence: 99%
“…The TCA cycle intermediates in the liver tissue (≈15 mg) and isolated mitochondrial protein (500 µg) were extracted with 750 µL of chloroform: methanol (2:1) and 250 µL of water. The aqueous phase was dried under nitrogen, and the TCA cycle intermediates were converted to their oximes with 20 µL of 2% methoxamine hydrochloride in pyridine ( w / v ) by microwaving for 90 s, which is followed by conversion to their respective TBDMS (Tert-butyldimethylsilyl) derivatives [ 42 ]. Serum (25 µL) samples were processed following deproteinization with 750 µL of cold acetonitrile and the conversion of metabolites to their oxime with 20 µL of 2% methoxamine hydrochloride in pyridine, followed by TBDMS derivatization.…”
Section: Methodsmentioning
confidence: 99%
“…Metabolites were separated on a HP-5MS UI column (30 m × 0.25 mm × 0.25 μm; Agilent, Santa Clara, CA, USA) and fragmented under electrical ionization. Fragments of interest were detected using single ion monitoring (SIM) on a GC-MS (5973N-Mass Selective Detector, 6890-Series GC, Agilent, Santa Clara, CA, USA) [ 42 ].…”
Section: Methodsmentioning
confidence: 99%